LEGAL REVIEW OF CHILD PROTECTION IN FULFILLING THEIR RIGHTS AFTER DIVORCE AND ITS IMPLEMENTATION IN MEDAN RELIGIOUS COURT DECISIONS - Agustira Sitorus; T. Riza Zarzani; Mhd. Azhali Siregar (PT. Sinergi Legal Publisher, 2025)
Divorce not only affects the husband and wife, but also has serious consequences for the children born from the marriage. One important aspect that must be considered after a divorce is the fulfillment of children's rights, especially regarding custody, maintenance, and affection from both parents. Although legal regulations in Indonesia, such as Law Number 1 of 1974 concerning Marriage, Law Number 35 of 2014 concerning Child Protection, and the Compilation of Islamic Law have clearly regulated the obligations of parents towards children after a divorce, the implementation of these regulations still faces various obstacles. Many cases show that fathers who are required to provide maintenance often avoid their responsibilities, which has a negative impact on the welfare of children. This study uses an empirical normative legal method with a statutory and comparative law approach to analyze the effectiveness of legal protection for children after divorce, especially in the Medan Religious Court decision. The results of the study indicate that although the court decision has determined the amount of maintenance that must be given, in practice the execution of the decision often encounters obstacles, both due to the low level of father compliance and weak law enforcement mechanisms. Therefore, a more effective policy reformulation is needed, including simplifying execution procedures, strengthening legal sanctions for negligent parents, and a more active role for the state in ensuring the fulfillment of children's rights. With these steps, it is hoped that children's rights after divorce can be protected more optimally, so that the welfare and legal certainty for children remain guaranteed.